2019
DOI: 10.1080/10428194.2019.1590569
|View full text |Cite
|
Sign up to set email alerts
|

Rates of deep molecular response by digital and conventional PCR with frontline nilotinib in newly diagnosed chronic myeloid leukemia: a landmark analysis

Abstract: ENESTnext (NCT01227577) was a single-arm, multicenter trial evaluating the rate of deep molecular response by 2 years in patients with newly diagnosed (within 6 months) chronic myeloid leukemia in chronic phase (CML-CP) treated with nilotinib 300 mg twice daily. Among 128 enrolled patients, 94 (73%) achieved major molecular response (MMR; BCR-ABL1 0.1% on the International Scale [BCR-ABL1 IS ]) and 34 (27%) achieved confirmed MR 4.5 (BCR-ABL1 IS 0.0032% detectable or undetectable; primary endpoint) by 2 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The increase in sensitivity makes dPCR also applicable for MRD monitoring and for the selection of patients with optimal chances of successful TKI treatment discontinuation, for both canonical and atypical BCR-ABL1 transcripts. 47,48,53 Only limited by the available sample size and the number of partitions, its sensitivity reaches levels of MR5.0 to MR6.0 with current protocols, which is a 1-log improvement compared to qPCR. While the depth of DMR assessed by qPCR was not predictive, several studies have shown a consistent predictive value of dPCR for successful TFR.…”
Section: Discussion: Is Digital Pcr Applicable In Clinical Practice?mentioning
confidence: 99%
“…The increase in sensitivity makes dPCR also applicable for MRD monitoring and for the selection of patients with optimal chances of successful TKI treatment discontinuation, for both canonical and atypical BCR-ABL1 transcripts. 47,48,53 Only limited by the available sample size and the number of partitions, its sensitivity reaches levels of MR5.0 to MR6.0 with current protocols, which is a 1-log improvement compared to qPCR. While the depth of DMR assessed by qPCR was not predictive, several studies have shown a consistent predictive value of dPCR for successful TFR.…”
Section: Discussion: Is Digital Pcr Applicable In Clinical Practice?mentioning
confidence: 99%
“…The application of the Fluidigm platform was also experienced by other groups, confirming the good accuracy and sensitivity of dPCR in the setting of BCR-ABL1 transcript measurement. In the ENEST next trial, which evaluated the rate of DMR in patients treated with nilotinib as first-line therapy, dPCR detected residual BCR-ABL1 transcripts in 39.4% of samples that were estimated to be in confirmed MR 4.5 [22] by RT-qPCR, thus demonstrating the feasibility of monitoring very low BCR-ABL1 transcript levels using dPCR [24].…”
Section: Mr Monitoringmentioning
confidence: 98%
“…In the context of the imatinib suspension and validation (ISAV) study (NCT01578213), ddPCR was able to detect one BCR-ABL1 positive cell out of 10 7 cells, predicting relapse in CML patients after imatinib discontinuation [13]. Moreover, Fluidigm digital PCR assay has been used in the ENESTnext (NCT01227577) study, confirming that ddPCR is more sensitive than RT-qPCR in patients with confirmed MR4.5, since about 40% of analyzed samples had a detectable BCR-ABL1 [26]. Our data also corroborated results previously obtained by Della Starza et al in pediatric acute lymphoblastic leukemia, where they identify ddPCR as more accurate than RT-qPCR in the measurement of MRD, particularly in the advanced follow-up [27].…”
Section: Discussionmentioning
confidence: 84%